ANALISIS PELAKSANAAN PROGRAM PENCEGAHAN PENANGGULANGAN HIV/AIDS (P2HA) DI PELABUHAN TELUK BAYUR KOTA PADANG - Ilma Nuria Sulrieni (Ensiklopedia of Journal, 2020)
Teluk Bayur Padang Seaport is potential risky place for HIV/AIDS transmission. P2HA program is a comprehensive, integrative, and effective method of approach to prevent sexual transmission collaborating with government, nongovernment institution and society. The aim of this research was to find out the implementation of HIV/AIDS program or P2HA in port area. This research used mix method: Quantitative approach using cross sectional using univariate analysis by distribution of frequencies and qualitative approach using FGD and in-depth interview. This research showed that condom availability is still low, only few outlets that accessible to workers and the use of condom is still low among man workers. The awareness to access health services is still low and HIV/AIDS socialization hasn’t been included in workers' preventive behaviors. It can be concluded that implementation of HIV/AIDS program by P2HA at seaport hasn’t worked well.